Special arithmetic and geometric means preserve ø like univalence (1978)
Let R be a region containing 0.Let   Ø be analytic, in R and satisfying Ø  (o) =  0 and  Re{ Ø  (0)} and gt; 0. Let D be the open unit disc of the complex plane centered at 0.